Brain Exercise Therapy Using Scrabble Board Game To Overcome Memory Impairment In Elderly With Dementia In The Working Area Of Tegal Selatan Community Health Center - Arriani Indrastuti; Ramadhan Putra Satria; Mohammad Chafif Auliya Khan (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: Dementia is a condition characterized by cognitive decline, which significantly impacts daily activities and social relationships. Memory loss is one of the earliest signs of dementia, and the elderly are particularly vulnerable to its onset. Brain exercises, such as those that activate both brain hemispheres, can help stimulate cognitive functions and improve brain activity. The Scrabble board game has been identified as an effective tool to enhance cognitive abilities, slow the progression of dementia, and provide mental stimulation. Objective:This study aims to assess the effectiveness of brain exercise activities and the Scrabble board game as therapeutic interventions for elderly individuals experiencing memory impairment in the Tegal Selatan Public Health Center area. Method: A case study approach was applied, focusing on two clients with memory impairment. Over one week, nursing care was provided, with data collected through interviews, direct observations, and the Mini-Mental State Examination (MMSE). Results:The integration of brain gym exercises and Scrabble board game therapy resulted in noticeable improvements in memory and cognitive function in both clients. After seven days of therapy, the first client's MMSE score increased from 16 (indicating moderate cognitive impairment) to 21, while the second client's score rose from 18 to 25, indicating no cognitive impairment. Conclusion:The combination of brain exercises and Scrabble therapy has proven beneficial in enhancing cognitive functions, particularly memory, in elderly individuals with dementia-related memory issues.